Mid-treatment Fluorodeoxyglucose Positron Emission Tomography in Human Papillomavirus-related Oropharyngeal Squamous Cell Carcinoma Treated with Primary Radiotherapy: Nodal Metabolic Response Rate can Predict Treatment Outcomes. Issue 12 (December 2021) - Lin, P.; Min, M.; Lai, K.; Lee, M.; Holloway, L.; Xuan, W.; Bray, V.; Fowler, A.; Lee, C.S.; Yong, J.
Abstract: Aims: To evaluate whether biomarkers derived from fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT) performed prior to (prePET) and during the third week (interim PET; iPET) of radiotherapy can predict treatment outcomes in human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma (OPC). Materials and methods: This retrospective analysis included 46 patients with newly diagnosed OPC treated with definitive (chemo)radiation and all patients had confirmed positive HPV status (HPV+OPC) based on p16 immunohistochemistry. The maximum standardised uptake value (SUVmax ), metabolic tumour volume (MTV) and total lesional glycolysis (TLG) of primary, index node (node with the highest TLG) and total lymph nodes and their median percentage (≥50%) reductions in iPET were analysed, and correlated with 5-year Kaplan–Meier and multivariable analyses (smoking, T4, N2b-3 and AJCC stage IV), including local failure-free survival, regional failure-free survival, locoregional failure-free survival (LRFFS), distant metastatic failure-free survival (DMFFS), disease-free survival (DFS) and overall survival. Results: There was no association of outcomes with prePET parameters observed on multivariate analysis. A complete metabolic response of primary tumour was seen in 13 patients; the negative predictive value for local failure was 100%. More than a 50% reduction in total nodal MTV provided the best predictor of outcomes, including LRFFS (88% versus 47.1%, P = 0.006, hazard ratio = 0.153) and DFS (78.2% versus 41.2%, P = 0.01, hazard ratio = 0.234). More than a 50% reduction in index node TLG was inversely related to DMFFS: a better nodal response was associated with a higher incidence of distant metastatic failure (66.7% versus 100%, P = 0.009, hazard ratio = 3.0). Conclusion: The reduction (≥50%) of volumetric nodal metabolic burden can potentially identify a subgroup of HPV+OPC patients at low risk of locoregional failure but inversely at higher risk of distant metastatic failure and may have a role in individualised adaptive radiotherapy and systemic therapy. Highlights: Latent and atypical distant failure pattern seen more commonly in HPV+OPC patients. Nodal metabolic response in third week of radiotherapy predicts better locoregional control. However, it is inversely associated with a higher risk of distant metastatic failure. FDG PET in third week of radiotherapy may have a role in individualised adaptive therapy. Unique tumour biology and radiation-induced immunogenicity to HPV+OPC.